Electric modeling and characterization of pulsed high‐voltage nanoelectrospray ionization sources by a miniature ion trap mass spectrometer. (17th June 2019) - Xu, Zuqiang; Wu, Hanyan; Tang, Yang; Xu, Wei; Zhai, Yanbing
Abstract: A better understanding of nanoelectrospray ionization (nano‐ESI) would be beneficial in further improving the performances of nano‐ESI. In this work, the pulsed high‐voltage (HV) nano‐ESI has been electrically modeled and then systematically characterized by both voltage‐current and mass spectrometry measurements. First, the equivalent resistance of a nano‐ESI source changes with respect to both emitter tip diameter and the HV applied. Increased voltage could improve both spray current and ionization efficiency of the pulsed HV nano‐ESI. Compared with conventional DC HV method, a pulsed HV has less heating effect on the capillary tip and thus allowing the application of a much higher voltage onto a nano‐ESI source. As a result, a pulsed HV nano‐ESI could further boost the ionization efficiency of nano‐ESI by employing even higher voltages than conventional DC nano‐ESI sources.